Regulation of neuritogenesis in hippocampal neurons using stiffness of extracellular microenvironment. - Aya Tanaka; Yuki Fujii; Nahoko Kasai; Takaharu Okajima; Hiroshi Nakashima (PLoS ONE, 2018)
The mechanosensitivity of neurons in the central nervous system (CNS) is an interesting issue as regards understanding neuronal development and designing compliant materials as neural interfaces between neurons and external devices for treating CNS injuries and disorders. Although neurite initiation from a cell body is known to be the first step towards forming a functional nervous network during development or regeneration, less is known about how the mechanical properties of the extracellular microenvironment affect neuritogenesis. Here, we investigated the filamentous actin (F-actin) cytoskeletal structures of neurons, which are a key factor in neuritogenesis, on gel substrates with a stiffness-controlled substrate, to reveal the relationship between substrate stiffness and neuritogenesis. We found that neuritogenesis was significantly suppressed on a gel substrate with an elastic modulus higher than the stiffness of in vivo brain. Fluorescent images of the F-actin cytoskeletal structures showed that the F-actin organization depended on the substrate stiffness. Circumferential actin meshworks and arcs were formed at the edge of the cell body on the stiff gel substrates unlike with soft substrates. The suppression of F-actin cytoskeleton formation improved neuritogenesis. The results indicate that the organization of neuronal F-actin cytoskeletons is strongly regulated by the mechanical properties of the surrounding environment, and the mechanically-induced F-actin cytoskeletons regulate neuritogenesis.